Ethnobotanical Study and Inventory of Medicinal Plants of Betawi Tribal Community in Kelurahan Ciracas, East Jakarta - Hadi, Achmad Syaiful; Rahayu, Sri Endarti; Saputro, Budiyono (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Research on ethnobotanical studies and inventories of medicinal plants in the Betawi tribal community in Kelurahan Ciracas, Kecamatan Ciracas, East Jakarta that has been carried out has the aim of obtaining information related to knowledge of medicinal plants, which include various types of medicinal plants, along with parts of medicinal plant organs used, and how to process them by the Betawi tribal community. The research method used is descriptive, with data collection techniques through observation, interviews, documentation, and identification. The data from the study were then analyzed descriptively and tabulated to show a description of the morphological characteristics of each type of medicinal plant found. The results showed that in Kelurahan Ciracas, there were 30 types of plants from 24 families that were used by the Betawi tribal community in the area as medicinal materials. Parts of medicinal plant organs utilized include roots, stems, leaves, tubers, and rhizomes. Meanwhile, the processing is carried out by boiling, pounding, mashing, and kneading. How to use it is done by drinking, pasting, smearing, and dripping on the body part that is sick or to be treated.